Pengaruh Literasi Media Digital dan Student Engagement Terhadap Hasil Belajar Ekonomi di Masa Pandemi Kelas X IPS di MAN 2 Kota Padang - Vina Khairunnisa; Rani Sofya (Jurnal Salingka Nagari, 2023)
The purpose of this research is to determine the impact of digital media literacy and student engagement on economic learning outcomes during the Class X IPS Pandemic Period at MAN 2 Padang City. The quantitative research method was used in this study, with descriptive and associative research types. This study included 174 students from class X IPS at MAN 2 Padang City. The sample in this study was measured using the Slovin formula, and the sampling technique was random, yielding a sample of 121 people. The data was analyzed using the SPSS program to test the hypothesis using validity and reliability tests, normality tests, multicollinearity, heteroscedasticity, multiple linear regression tests, F tests, and t-tests. The study's findings indicate that (1) digital media literacy has no effect on student learning outcomes, (2) student engagement influences student learning outcomes, and (3) digital media literacy and student engagement influence student economic learning outcomes.